مداخل تطوير الدَّرس العقدي من خلال التراث العقدي بالغرب الإسلامي: Approaches for Development of Studying Doctrine through Doctrine Heritage in Muslim West - مبركي, عمر (Al-Fikr al-islāmī al-muʿāṣir (previously Islamiyat al-Ma'rifah), 2019)
This paper presents an overview description of the actual state of studying Islamic Doctrine by shedding light on some problematic issues that negatively affect the purpose of its study, such as keeping pace with the latest developments in life, and addressing the challenges and suspicions facing the Muslim of today and threatening his faith and values. The present paper has two parts, the first is devoted to the most important problems related to the study of Islamic Doctrine, with special focus on three of them: the complexity and abstraction, the detachment of doctrinal theories from reality, and the week link to the Qur'anic approach in addressing monotheistic demands. The second part provides suggestions of necessary approaches to develop the study that would overcome its problems, based on illuminating examples of the doctrinal heritage in the Islamic West.